Natural Killers Are Made Not Born: How to Exploit NK Cells in Lung Malignancies - Carrega, Paolo; Ferlazzo, Guido (Frontiers in Immunology, 2017)
In recent years, progress has been made in the characterization of natural killer (NK) cells in lung malignancies and we have now gained a better understanding of the frequency, localization, phenotype and functional status of NK cells infiltrating these tumors. NK cell subset recruited in lung cancer is mainly capable of producing relevant cytokines rather than exerting direct cancer cell killing. Thus, the relevance of NK cells in tumor microenvironment might also go beyond the killing of tumor cells, being NK cells endowed with regulatory functions toward an ample array of immune effectors. Nevertheless, boosting their cytotoxic functions and redirecting the migration of cytotoxic NK cell subset to the tumor site might open new therapeutic avenues for lung cancer. Also, we believe that a deeper investigation into the impact of both conventional (e.g. chemotherapy) or new therapies (e.g. anti-immune checkpoints mAbs) on NK cell homeostasis in lung cancer patients is now required.